Veränderungen im Bereich des Lehrens und Lernens von Sprachen und deren Konsequenzen für die Aus- und Fortbildung von Fremdsprachenlehrerinnen - Krumm, Hans-Jürgen (Neofilolog, 2019)
The world is changing. Is the teaching of foreign languages also bound to change? The answer to the question is not about confirming that almost all learners have their smartphones now. After all, language teaching is not aimed at following all new fashion trends. The decisive factor is the fact that today's learners are different from those 10 or 15 years back. They are characterised by growing linguistic (and usually also cultural) diversity, their network of contacts with the world, family relationships and personal experiences are more diversified and colourful. Also, requirements towards them change: they need to be able to adapt to the rapidly developing world, the world of globalisation and of nationalistic tendencies. How can foreign language education contribute to their finding their place in a society of open borders, linguistic and cultural diversity, and new possibilities offered to each of them? In response to the question, the author encourages everyone to ponder on the following topics: How do learners contribute to the learning process and foreign language instruction: diversity as capital Plurilingualism is the main principle of language education and school development Action-based vs. task-based: how autonomous can learners be? Learning on the Web: foreign languages are learnt not only during lessons Professional development and reflection as the essence of teaching competence in a contemporary school